Avaliação da atividade antioxidante em ratos com neurotoxicidade induzida pela proteína β-amilóide (aβ) e suplementados com extrato de yacon (Smallanthus sonchifolius) - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Alzheimer's disease (AD) is considered to be a more common neurodegenerative disorder in the world, with the elderly being over 65 years old, in whom the central nervous system is compromised. AD is recognized by memory deficit and decline in reasoning ability. Oxidative stress plays an important role in the development and progression of AD, and antioxidants may be relevant in the prevention and treatment of the disease, resulting in yacon, a tuberous root originated from the Andean region, rich in fructooligosaccharides (FOS) and a compounds. Popularly the root is consumed in natura and as leaves in the way of making the treatment of diabetes and cholesterol disorder. However, little is said about the other properties of the plant. Thus, the objective of this work was to investigate the neuroprotective effects of yacon on Aβ-induced neurotoxicity in Wistar rats supplemented with leaf extract and yacon root. The animals in the supplemented groups received the probe extract for 14 consecutive days, on January 15, 1997, when they underwent intraocular β-amyloid (Aβ) injection surgery. Supplementation was performed for more than 10 days after the animals were euthanized. Antioxidant defense markers (CAT, SOD and GPx) were evaluated in the hippocampus through classical methodologies. The results obtained were a statistically significant (p <0.05) significant of the antioxidants (CAT, SOD and GPx) without hippocampus of rats treated with leaf extract and yacon root in relation to the other groups. Therefore, a possible neuroprotective effect of yacon extract is suggested, since oxidative stress is one of the main causes / consequences of AD neurotoxicity and progression.
Evaluation of antioxidant activity in rats with neurotoxicity induced by β-amyloid protein (aβ) and supplemented with yacon extract (Smallanthus sonchifolius)
Keywords: Defesas antioxidantes; Yacon; Alzheimer's; Antioxidant defenses; Doença de Alzheimer; Alzheimer; Smallanthus sonchifolius; Alzheimer's disease; CNPQ::CIENCIAS DA SAUDE